Degradation Analyses Defining of The Test Parameters In Orbit To Optical Solar Reflector for Space Use - Boato, Marcos Galante; Garcia, Ezio Castejon; Cione, Francisco Carlos; Oliveira, Mauro Machado de (Revista para Graduandos/Instituto Federal de Educação, Ciência e Tecnologia de São Paulo - Campus São Paulo - REGRASP, 2022)
Abstract –Optical Solar Reflector (OSR) is a thermal control material utilized in the majority of the satellite to world and also was developed in Brazil as an alternative to be used in the special program. OSR is a passive radiator, applying it as a coating on the outside walls in order to reject the heat generated internally to the satellite to the space environment. This type of radiator has a low absorptivity in the solar spectrum (?s) and a high emissivity in the infrared spectrum (?IR). However, the degradation caused by the space environment increases the demanding and consequently reduces the efficiency of the radiator. We are designing an experiment to test in orbit one OSR developed at the National Institute for Space Research aimed, among other objectives, to evaluate their degradation when exposed to the space environment. The experiment should be exposed to solar radiation and having its monitored temperature and, based on this, determining the variation of the ?s as the increase of the OSR’ degradation over time. An analysis using the mathematical program SINDA/FLUINT was made in order to determine the relationship of increased temperature radiator with increasing the ?s. This article presents the results of this exploratory analysis and the experiment viability conditions.